The Implementation of Scientific Crime Investigation Mechanisms in Police Regional Office Proof Criminal Cases - Anggraeny, Kurnia Dewi; Rizqullah, Alfan Noufal; Nur, Muhammad (IJCLS (Indonesian Journal of Criminal Law Studies), 2024)
Investigation is a critical stage in criminal proceedings aimed at uncovering evidence to illuminate the nature of an offense and identify its perpetrator or suspect. The application of Scientific Crime Investigation (SCI) methods in these investigations leverages a scientific approach drawn from diverse disciplines to enhance the collection and analysis of evidence. This study seeks to underscore the importance of integrating SCI into the substantiation of criminal cases and explore its operational implementation within police regional offices. This empirical juridical research draws upon library materials and field studies to examine the urgency and efficacy of SCI in criminal investigations. Data analysis employs a descriptive-qualitative method to elucidate how the SCI method functions as a systematic tool in gathering evidence crucial for courtroom presentation. The evidentiary robustness of SCI findings, including expert testimonies and forensic reports, lends them substantial weight as incontrovertible evidence obtained through rigorous scientific processes. Aligned with legal theories such as bewisjmidellen, bewijsmnimum, negatief wettelijk bewijstheorie, bewisjkracht, and bewijsvoering, the SCI method encompasses several key components: 1) Identification, involving the examination of fingerprints to establish identities; 2) Digital forensics, for analyzing electronic and digital evidence; 3) Forensic psychology, aiding in the assessment of psychological states of victims, witnesses, and perpetrators; and 4) Forensic medicine, facilitating examinations related to injuries, poisoning, or fatalities conducted by forensic physicians. Each phase of the SCI method adheres rigorously to legal frameworks and procedural guidelines. By integrating these specialized disciplines, SCI enhances the investigative process, ensuring thoroughness and credibility in the pursuit of justice within the bounds of the law.